Conception of The Precautionary Principle in International Environmental Law: Ecosystem or Humanity? - Pebrianto, Dony Yusra; Putra, Akbar Kurnia; Ardianto, Budi (Uti Possidetis: Journal of International Law, 2024)
This paper discusses the concept of the precautionary principle as a bridge between the dichotomy of ecosystem protection and human safety. A pertinent example is the proposed evacuation road in Kerinci, which has yet to receive permission due to its planned route through Kerinci Seblat National Park. The issue is analyzed using a normative approach. The research concludes that the precautionary principle establishes a balance between the objectives of ecosystem safety and human safety as a fundamental right. Therefore, the state must not neglect its responsibilities and should maintain oversight of all policies, ensuring that prior decisions are guided by stringent risk analysis. This approach emphasizes the importance of integrating ecological considerations into development policies, ultimately aiming for sustainable coexistence between human needs and environmental preservation.